Pengaruh Net Profit Margin dan Total Asset Turnover Terhadap Return On Assets Pada PT. Astra International Tbk Periode 2001 – 2008. - Syafruddin, Syafruddin (Universitas Muhammadiyah Prof. DR. HAMKA, 2016)
This thesis aims to determine the effect on net profit margin of return on assets, total asset turnover of return on assets, as well as between the net profit margin and total asset turnover is common - equal to the return on assets. The hypothesis tested is: there is a positive influence and a significant net profit margin of return on assets. There is a positive influence and a significant total asset turnover of return on assets. There is a positive influence and significantly between the net profit margin and total assets turnover is common - equal to the return on assets. The method used in this research is descriptive method and verifikatif. Population in this research is PT. Astra International Tbk. And the sample of Financial Statements and Loss Balance Sheet - Profit .. Data were analyzed with descriptive statistics, for statistical hypothesis testing used a simple correlation, multiple and partial and multiple regression.The results showed that: First, there is a positive influence and a significant net profit margin of return on assets, with a correlation coefficient of ry1 = 0.694 ? = 0.05 level. Second, there is a positive influence and a significant total asset turnover of return on assets, ry2 correlation coefficient = 0.754 at ? = 0.05 level. Third, there is a positive influence and significantly between the net profit margin and total asset turnover is common - equal to the return on assets by the regression equation Y = - 0.046 + 0.504 X1 + 0.095 X2, Ry1.2 correlation coefficient = 0.951 at the level of ? =  0, 05.The results of this study are expected to be useful for the improvement of the quality of financial reports of PT. Astra International Tbk to consider this conclusion. That the return on assets (Y) can be increased by increasing the net profit margin (X1) and Total Assets Turnover (X2).